The jurisprudential doctrine and the constitutional binding precedent: an approach to the constitutional jurisprudence from the theory of sources of law - Indacochea Prevost, Ursula (2015)
The debate on how to understand the legal figureof “jurisprudence” is still relevant in Constitutional Law and, in general, in the Theory of Law, in countries where the legal system follows Civil Lawand also in those that are under Common Lawsystems.The Peruvian Constitutional Procedure Code has introduced in its Preliminary Title two figures that are related to constitutional jurisprudence: the jurisprudential doctrine and the constitutional binding precedent.In the present article, the author makes an approach to both figures from the theory of the sources of Law. She presents an overview on how the “production of Law” is understood in doctrine, and on how the constitutional jurisprudence could take a place in this order, taking into account the form in which the role of the Judge is considered.